2012
DOI: 10.1111/j.1745-4557.2011.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Utilization of Protein Derived From Surimi Wash‐water

Abstract: Surimi processors are committed to improve utilization of seafood resources, increase productivity and reduce organic matter discharged into the environment. The object of this study was to recover protein from pollock surimi processing washwater using membrane filtration and characterize properties of the recovered material. A pilot unit equipped with membrane elements concentrated protein from the surimi wash-water. Membrane concentrate and control surimi samples were analyzed for proximate composition, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…Analysis of proximate composition of material recovered from surimi processing waste streams indicated moisture making up that majority of the recovered solid at 86.70%, followed by protein at 14.21% (Stine et al., ). Wibowo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of proximate composition of material recovered from surimi processing waste streams indicated moisture making up that majority of the recovered solid at 86.70%, followed by protein at 14.21% (Stine et al., ). Wibowo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to find out new efficient technologies for these by-products, with environmentally sound procedures requiring low energy consumption (Dumay et al , 2008; Stine et al , 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The recovery of proteins may potentially improve yield beyond recycle the water from surimi obtaining processes (Lin et al , 1995) and them added back at a low percentage to surimi products (Stine et al , 2012). Numerous studies have been published on recovering proteins from surimi process (Bourtoom et al , 2009; Dumay et al , 2008; Lin et al , 1995; Rawdkuen et al , 2009; Sanmartín et al , 2009; Stine et al , 2012; Velazquez et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-known example is the wash water from surimi production. Stine et al [13] showed that proteins in such wastewater could be recovered and added back to the surimi without affecting the end-product quality. Another type of product which, during production, generates large amount of liquid waste is the marinated herring, a traditional Scandinavian product.…”
Section: Introductionmentioning
confidence: 99%